Reforming the International Monetary and Financial System. (International Monetary Fund, 2000)
This volume examines the implications of greater financial integration on the international monetary and financial system, and how it should be reformed. Various experts consider the most disruptive manifestations of instability and the appropriate policy responses, including exchange rate volatility and misalignments; unstable capital flows to emerging market economies; abrupt capital flow reversals; and private sector involvement in crisis resolution. The IMF's role in crisis prevention and resolution is also examined.